RANCANG BANGUN SISTEM PENYEDIA DATA HiRID MTSAT-1R - - Suhermanto (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2008)
On the transition of operational Geostationary Meteorological Satellite GMS-5 to MTSAT-1R, HiRID’s data packet was introduced. HiRID uses the same frame as of the S-VISSR, with some modifications to accommodate the additional information because of performance improvement of its data imaging system. Performance improvement of instrument is associated with addition of IR4 channel and radiometric resolution improvement of infrared channel to 10 bits/ pixel. The operating lifetime of HiRID as transition data packet to the MTSAT-1R HRIT is limited in the view of giving a grace period to the Earth station operators to upgrade the receiving systems towards HRIT operationalization. This paper reviews the efforts to obtain MTSAT-1R HiRID data and adjustments made in the sub-receiver systems, sub-system of data pre-processing. The discussion includes a glance of RF system integration, data extraction techniques and information extraction of documentation sector, focusing the discussion on the different of structures of HiRID data packets and S-VISSR as well as techniques that are applied to extract image data and any information contained therein. Keyword:S-VISSR, HiRID, Sub-commutation, Decomposition